Trainee burnout: when does the fire start?. Issue 1156 (4th November 2020) - Robinson, David Bryan Thomas; James, Osian Penri; Hopkins, Luke; Brown, Chris; Powell, Arfon; Abdelrahman, Tarig; Egan, Richard John; Lewis, Wyn
Abstract: Purpose of the study: Burnout is an increasingly recognised phenomenon in acute healthcare specialities and associated with depersonalisation, ill health and training programme attrition. This study aimed to quantify contributory physiological variables that may indicate stress in newly qualified doctors. Study design: Post Graduate Year 1 doctors (n=13, 7 f, 6 m) were fitted with a VivaLNK wellness device during four prior induction days, followed by their first 14 days work as qualified doctors. Minute-by-minute Heart Rate (HR), Respiratory Rate (RR), and Stress Index (SI) data were correlated with Maslach Burnout Inventories, Short Grit Scales (SGS) and clinical rota duties: Induction vs Normal Working-Day (NWD) versus On-call shift. Results: In a total 125 recorded shift episodes, on comparing Induction versus NWD versus On-call shift work, no variation was observed in HR above baseline (25.47 vs 27.14 vs 24.34, p=0.240), RR above baseline (2.21 vs 1.86 vs 1.54, p=0.126) or SI (32.98 vs 38.02 vs 35.47, p=0.449). However, analysis of participant-specific temporal SIs correlated with shift-related clinical duties; that is, study participants who were most stressed during a NWD, were also more stressed during Induction (R 2 0.442, p=0.026), and also during On-call shifts (R 2 0.564, p=0.012). Higher SGS scores were inversely related to lower SIs (coefficient −32.52, 95% CI −45.881 to 19.154, p=0.001). Conclusion: Stress and burnout stimulus appear to start on day one of induction for susceptible PGY1 doctors, and continues into front-line clinical work irrespective of shift pattern. Short Grit Scale questionnaires appear an effective tool to facilitate targeted stress countermeasures.